2022
DOI: 10.1186/s40594-021-00322-y
|View full text |Cite
|
Sign up to set email alerts
|

Exploring students’ procedural flexibility in three countries

Abstract: Background In this cross-national study, Spanish, Finnish, and Swedish middle and high school students’ procedural flexibility was examined, with the specific intent of determining whether and how students’ equation-solving accuracy and flexibility varied by country, age, and/or academic track. The 791 student participants were asked to solve twelve linear equations, provide multiple strategies for each equation, and select the best strategy from among their own strategies. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(46 citation statements)
references
References 54 publications
1
42
1
Order By: Relevance
“…For example, according to Xu et al (2017), if a student solved the equation in Table 1 using the two strategies shown and then identified Strategy 2 as the best one, then the student was recognized as having chosen the appropriate strategy for this problem. Specifically, in Xu et al (2017) (see also Star & Seifert, 2006;Star et al, 2022;Rittle-Johnson & Star, 2007), Strategy 2 is considered a more appropriate strategy in this particular task context because it reduces computational steps (Star & Seifert, 2006). A flexible problem solver should be able to solve equations such as the one shown in Table 1 using multiple ways and to identify that Strategy 2 is more appropriate (Liu et al, 2018;Xu et al, 2017).…”
Section: Evaluating the Appropriateness Of Strategies: The Importance...mentioning
confidence: 99%
“…For example, according to Xu et al (2017), if a student solved the equation in Table 1 using the two strategies shown and then identified Strategy 2 as the best one, then the student was recognized as having chosen the appropriate strategy for this problem. Specifically, in Xu et al (2017) (see also Star & Seifert, 2006;Star et al, 2022;Rittle-Johnson & Star, 2007), Strategy 2 is considered a more appropriate strategy in this particular task context because it reduces computational steps (Star & Seifert, 2006). A flexible problem solver should be able to solve equations such as the one shown in Table 1 using multiple ways and to identify that Strategy 2 is more appropriate (Liu et al, 2018;Xu et al, 2017).…”
Section: Evaluating the Appropriateness Of Strategies: The Importance...mentioning
confidence: 99%
“…Among other possible strategies, some are arguably better than the standard algorithm, where better (or "situational ly appropriate"; Star et al, 2022) may mean that the strategy is more elegant and/or better matched to the structural features of the problem. To illustrate, for the above equation 3(x + 1) = 15, an arguably better strategy would involve dividing both sides of the equation by 3 as a first step.…”
Section: Relationships Between Strategy Appropriateness and Strategy ...mentioning
confidence: 99%
“…Student-problems were coded as better-than-standard if their approach demonstrated more elegance and innovation than the standard approach, based on similar determinations in prior studies (e.g., Star & Seifert, 2006;Star et al, 2022). For example, for Question 2, if a student divided by 3 as a first step, this was considered a better-than-standard strategy because the strategy takes advantage of the structural features of the problem (15 is evenly divisible by 3) and can be solved in fewer steps.…”
Section: Codingmentioning
confidence: 99%
See 1 more Smart Citation
“…One factor that impacts students' ability to think creatively is their content and domain knowledge (Baer and Garrett, 2010). Although higher grades are not guaranteed to equate to greater content knowledge, students gain experience with mathematical concepts across grade level and this content knowledge builds upon each other and improves the ability to think flexibly about mathematical concepts (Star et al, 2022). Hence, greater experience may boost mathematical creativity, as it provides more content to draw from when asked to generate new ways to solve a problem.…”
Section: Introductionmentioning
confidence: 99%